Expand menu menu_open Minimize Go to startpage home Home History history History expand_more
{{ item.displayTitle }}
navigate_next
No history yet!
Progress & Statistics equalizer Progress expand_more
Student
navigate_next
Teacher
navigate_next
{{ filterOption.label }}
{{ item.displayTitle }}
{{ item.subject.displayTitle }}
arrow_forward
No results
{{ searchError }}
search
menu
{{ courseTrack.displayTitle }} {{ printedBook.courseTrack.name }} {{ printedBook.name }}
{{ statistics.percent }}% Sign in to view progress
search Use offline Tools apps
Digital tools Graphing calculator Geometry 3D Graphing calculator Geogebra Classic Mathleaks Calculator Codewindow
Course & Book Compare textbook Studymode Stop studymode Print course
Tutorials Video tutorials Formulary

Video tutorials

How Mathleaks works

Mathleaks Courses

How Mathleaks works

play_circle_outline
Study with a textbook

Mathleaks Courses

How to connect a textbook

play_circle_outline

Mathleaks Courses

Find textbook solutions in the app

play_circle_outline
Tools for students & teachers

Mathleaks Courses

Share statistics with a teacher

play_circle_outline

Mathleaks Courses

How to create and administrate classes

play_circle_outline

Mathleaks Courses

How to print out course materials

play_circle_outline

Formulary

Formulary for text courses looks_one

Course 1

looks_two

Course 2

looks_3

Course 3

looks_4

Course 4

looks_5

Course 5

Login account_circle menu_open

Solving Exponential Equations

Exponential equations — equations in which the independent variable is an exponent — can be solved graphically and algebraically. Depending on the equation, different algebraic approaches can be used.
Method

Solving Exponential Equations Graphically

If the dependent variable of an exponential function written in the form y=abx, y = a \cdot b^x, is exchanged for a constant, say C,C, the result is a one-variable equation: C=abx. C = a \cdot b^x.

This type of equation is called an exponential equation, and can be solved graphically. This is done by first graphing the function y=abx,y = a \cdot b^x, then finding the xx-coordinate of the point(s) on the graph with the yy-coordinate C.C. The xx-coordinate(s) is the solution to the equation.
Exercise

Use the graph to solve the equation 3=50.85x.3 = 5 \cdot 0.85^x.

Solution

The graph shows all xx-yy points that satisfy the function rule y=50.85x.y = 5 \cdot 0.85^x. Let's compare the function rule and the equation. Function rule:y=50.85xEquation:3=50.85x\begin{aligned} \textbf{Function rule:} \quad y = 5 \cdot 0.85^x\\ \textbf{Equation:} \quad 3 = 5 \cdot 0.85^x \end{aligned} The only difference between these two equalities is that the independent variable, y,y, is replaced by a 33 in the equation. Thus, we solve the equation by finding the xx-coordinate of any point on the graph that has the yy-coordinate 3.3.

We can identify one such point in the graph. Let's now find the xx-coordinate of this point graphically.

This xx-coordinate is not easily read from the graph, so we'll have to make an approximation. It's just a bit bigger than 3,3, so we'll use 3.1.3.1. This means that an approximate solution to the equation is x3.1.x \approx 3.1. We can verify this by substituting it into equation to see if a true statement is made.

3=50.85x3 = 5 \cdot 0.85^x
x3.1x \approx {\color{#0000FF}{3.1}}
3?50.853.13 \overset{?}{\approx} 5 \cdot 0.85^{{\color{#0000FF}{3.1}}}
33.021123 \approx 3.02112 \ldots

The right-hand side and the left-hand side are approximately equal, so we have indeed found an approximate solution to the equation: x3.1.x \approx 3.1.

info Show solution Show solution
Method

Solving Exponential Equations with the Same Base

There are different ways to algebraically solve exponential equations. If both sides of the equation can be written in the same base, equality can be used. For example, consider the equation 42x=642. 4^{2x}=64^2. Since 64=43,64=4^3, the equation can be written as follows. 42x=(43)242x=46\begin{aligned} 4^{2x} &=\left({\color{#0000FF}{4^3}} \right)^{2}\\ 4^{2x} &=4^6\\ \end{aligned} Now, we have two equivalent expressions with the same base. For the equality to hold, the exponents must also be equal. Thus,

2x=6x=3. 2x=6 \quad \Leftrightarrow \quad x=3.
Exercise

Solve the equation 35x3=3-2x+11. 3^{5x-3}=3^{\text{-}2x+11}.

Solution
To begin, notice that both sides of the equation are exponential expressions with base 3.3. Since they have the same base, the exponents must be equal. This gives the equivalent equation 5x3=-2x+11, 5x-3=\text{-}2x+11, which we can solve using inverse operations.
5x3=-2x+115x-3=\text{-}2x+11
7x3=117x-3=11
7x=147x=14
x=2x=2
The solution to the equation is x=2.x=2.
info Show solution Show solution
{{ 'mldesktop-placeholder-grade-tab' | message }}
{{ 'mldesktop-placeholder-grade' | message }} {{ article.displayTitle }}!
{{ grade.displayTitle }}
{{ exercise.headTitle }}
{{ 'ml-tooltip-premium-exercise' | message }}
{{ 'ml-tooltip-programming-exercise' | message }} {{ 'course' | message }} {{ exercise.course }}
Test
{{ 'ml-heading-exercise' | message }} {{ focusmode.exercise.exerciseName }}
{{ 'ml-btn-previous-exercise' | message }} arrow_back {{ 'ml-btn-next-exercise' | message }} arrow_forward